Developing “hot-loop”-inspired cyclic peptides to inhibit the oncogenic Skp2-Cks1 protein-protein interaction. - Keenan, Caitlin M. (Tufts Archival Research Center, 2016)
This work involves using insight from a bioinformatics tool, LoopFinder, to design and test cyclic peptide inhibitors of a protein-protein interaction that is involved in cell cycle regulation and various types of cancer.